Evaluation of the impacts of polymeric fibers and modifiers on the fracture properties of asphalt mixtures - Niloofar Esmaeili; Mohammad Zia Alavi; Mahdi Samadzad (Results in Engineering)
Cracking is one of the primary distresses in asphalt pavements, and aging is recognized as a key factor that exacerbates this issue. The use of modifiers to improve the fracture resistance of pavements has long been common practice. The objective of this research was to examine the effects of aging and polymeric additives-such as SBS, crumb rubber, and double-twisted polyester fiber-on the fracture behavior of asphalt mixtures. The study was conducted under fracture Modes I and mixed Mode I/II, using the Semi-Circular Bend (SCB) test, with specimens featuring notch depths of 10, 20, and 30 mm. Evaluation of the mixtures was performed by comparing well-known fracture behavior indicators such as peak load, fracture energy, and others, as well as the damage transition point introduced in this study. The results showed that the addition of fibers increased the fracture resistance of the mixtures, leading to a significant rise in post-peak fracture energy. The use of crumb rubber and SBS as asphalt binder modifiers increased the peak load and fracture energy but reduced the flexibility of the mixtures due to a decrease in the homogeneity of the modified asphalt. Polymers had a greater impact on the pre-peak region compared to fibers, causing a more substantial increase in fracture energy in this area than in the post-peak region. The findings also indicated that the DTP parameter could effectively characterize the evolution of damage in asphalt mixtures in the pre-peak region and align with the results obtained from the previously established fracture parameters.